Perfects in Indo-European languages and beyond - Crellin, Robert Samuel David; Jügel, Thomas (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2020)
"This volume provides a detailed investigation of perfects from all the branches of the Indo-European language family, in some cases representing the first ever comprehensive description. Thorough philological examinations result in empirically well-founded analyses illustrated by over 940 examples. The unique temporal depth and diatopic breadth of attested Indo-European languages permits the investigation both of TAME (Tense-Aspect-Mood-Evidentiality) systems over time and of recurring cycles of change as well as synchronic patterns of areal distribution and contact phenomena, possibilities fully exploited in the volume. Furthermore, the cross-linguistic perspective adopted by many authors, as well as the inclusion of contributions which go beyond the boundaries of the Indo-European family per se, facilitates typological comparison. As such, the volume is intended to serve as a springboard for future research both into the semantics of the perfect in Indo-European itself, and verb systems across the world's languages"--